Priorities for the development of the social field in Ukraine and its legal regulation in the context of adaptation to European standards - Tetiana Dulik; Tetiana Aleksandriuk; Viktoriia Taranenko; Tetiana Koriahina; Vita Cherba (Universidad Hemisferios, 2023)
A functioning democratic regime that can meet the basic needs of citizens and guarantee material security for the vulnerable and most vulnerable segments of the population is the primary foundation of the European path of development of Ukraine. The purpose of this paper is to analyse the key goals of the state social policy of Ukraine in the context of the implementation of European Union standards and examine the current state of implementation of declared social and legal principles on the territory of the Ukrainian state. The leading methods of the study were methods of analysis and generalisation, through which the existing conflicts of the normative foundation in the field of social protection were identified, and a comparison method, the use of which demonstrated the existing shortcomings of the development strategy. investigating social priorities, the authors identify the main strategic goals of state social regulation, the main omissions of modern social policy, and the primary causes of the current social crisis. Therewith, the current state of the legislative social framework is investigated and an objective assessment of the implementation of European legislation in the national regulatory field of Ukraine is provided. Therewith, positive trends in establishing social justice by declaring gender equality and overcoming discrimination and integrating information systems into the provision of social services were analysed, and practical recommendations for successful euro adaptation, the decisive task of which is to improve the quality of life of Ukrainian citizens, were provided